2008
DOI: 10.1080/02713680802447121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Daily Prolonged Ketamine Anesthesia on Intraocular Pressure in Monkeys

Abstract: Purpose-To determine if repeated intramuscular ketamine in monkeys on consecutive days affects intraocular pressure (IOP), and if the ketamine-induced IOP change has any relationship to systemic dehydration and/or changes in mean arterial pressure (MAP) of the animals.Methods-Nine monkeys were studied per 4 protocols. IOP was determined hourly for 6-hrs by Goldmann tonometry under ketamine anesthesia on 3 (protocol 1) or 5 (protocols 2 and 3) consecutive days, or on alternating days 1, 3 and 5 (protocol 4). Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
7
1
1
Order By: Relevance
“…Because almost all agents for general anesthesia affect the IOP in both humans and animals (Almeida et al, 2004; Artru, 1995; Ausinsch et al, 1975; 1976; 1977; Adams and Barnett, 1966; Badrinath et al, 1986; Bito et al, 1979; Burke and Potter, 1986; Bunch et al, 2008; Camras et al, 2010; Erickson–Lamy et al, 1984; Gelatt et al, 1977; 1982; Hahneberger, 1976; Hahnenberger 1976a; 1976b; Hayreh et al, 1991; Hofmeister et al, 2006; 2008; Jia et al, 2000; Johnson et al, 2008; Komaromy et al, 1998; Krupin et al, 1980; Mirakhur et al, 1990; Mowafi et al, 2003; Murphy, 1985; Nagdeve et al, 2006; Sator-Katzenschlager et al, 2002; Schäfer et al, 2002; Schnell et al, 1996) and the repetitive use of anesthetics might cause either neuronal degeneration (Istaphanous and Loepke, 2009; Mellon et al, 2007) or neuroprotection (Hudetz and Pagel, 2010; Koerner and Brambrink, 2006; Mortier et al, 2000) in glaucomatous retina, measuring IOP from conscious animals would avoid the un-wanted effects of anesthetics on the IOP measurement and potential anesthesia-induced confounding of experimental results. Towards this end, measuring conscious IOP in rats after behavioral training seems to provide a reliable measurement of IOP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because almost all agents for general anesthesia affect the IOP in both humans and animals (Almeida et al, 2004; Artru, 1995; Ausinsch et al, 1975; 1976; 1977; Adams and Barnett, 1966; Badrinath et al, 1986; Bito et al, 1979; Burke and Potter, 1986; Bunch et al, 2008; Camras et al, 2010; Erickson–Lamy et al, 1984; Gelatt et al, 1977; 1982; Hahneberger, 1976; Hahnenberger 1976a; 1976b; Hayreh et al, 1991; Hofmeister et al, 2006; 2008; Jia et al, 2000; Johnson et al, 2008; Komaromy et al, 1998; Krupin et al, 1980; Mirakhur et al, 1990; Mowafi et al, 2003; Murphy, 1985; Nagdeve et al, 2006; Sator-Katzenschlager et al, 2002; Schäfer et al, 2002; Schnell et al, 1996) and the repetitive use of anesthetics might cause either neuronal degeneration (Istaphanous and Loepke, 2009; Mellon et al, 2007) or neuroprotection (Hudetz and Pagel, 2010; Koerner and Brambrink, 2006; Mortier et al, 2000) in glaucomatous retina, measuring IOP from conscious animals would avoid the un-wanted effects of anesthetics on the IOP measurement and potential anesthesia-induced confounding of experimental results. Towards this end, measuring conscious IOP in rats after behavioral training seems to provide a reliable measurement of IOP.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have shown that various anesthetics could alter IOP in humans (Ausinsch et al, 1975; 1976; 1977; Adams and Barnett, 1966; Badrinath et al, 1986; Mirakhur et al, 1990; Mowafi et al, 2003; Murphy, 1985; Nagdeve et al, 2006; Sator-Katzenschlager et al, 2002; Schäfer et al, 2002), monkeys (Bito et al, 1979; Burke and Potter, 1986; Bunch et al, 2008; Erickson–Lamy et al, 1984; Hahneberger, 1976; Hahnenberger 1976a; Hayreh et al, 1991; Komaromy et al, 1998; Krupin et al, 1980), dogs (Almeida et al, 2004; Artru, 1995; Gelatt et al, 1977; 1982; Hofmeister et al, 2006; 2008), cats (Burke and Potter, 1986; Hahnenberger, 1976b), rabbits (Burke and Potter, 1986; Schnell et al, 1996), rats (Jia et al, 2000), and mice (Camras et al, 2010; Jia et al, 2000; Johnson et al, 2008). Most of the anesthetics have been reported to decrease IOP in human and other animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cynomolgus (also known as the crabeating macaque, Macaca fascicularis) and Rhesus macaque (Macaca mulatta) are the most widely used and best studied. Their close phylogeny and high homology with humans makes them excellent test species and their responsiveness to [69][70][71][72][73][74][75][76][77][78]. Important differences between macaques and humans do exist, however, including a smaller corneal surface area and overall body mass which may affect the pharmacokinetics, ADME, and systemic toxicity of topically applied anti-glaucoma drugs.…”
Section: Species Selectionmentioning
confidence: 95%
“…Os animais permanecem com olhos abertos, apresentando bom tônus nos músculos mandibulares, com reflexos laringeais e faringeais ativos, enquanto que a analgesia aparenta ser extremamente boa (HALL e CLARCK, 2001;BUNCH et al, 2008).…”
Section: Na Eletroencefalografia (Eec) Há Evidencia De Dissociação Eunclassified